2012
DOI: 10.1002/jbmr.1740
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23 inhibits extrarenal synthesis of 1,25-dihydroxyvitamin D in human monocytes

Abstract: Vitamin D is a potent stimulator of monocyte innate immunity, with this effect being mediated via intracrine conversion of 25-hydroxyvitamin D (25OHD) to 1,25-dihydroxyvitamin D (1,25(OH)2D). In the kidney synthesis of 1,25(OH)2D is suppressed by fibroblast growth factor 23 (FGF23), via transcriptional suppression of the vitamin D-activating enzyme 1α-hydroxylase (CYP27B1). We hypothesized that FGF23 also suppresses CYP27B1 in monocytes, with concomitant effects on intracrine responses to 1,25(OH)2D. Monocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 66 publications
(147 reference statements)
3
126
1
Order By: Relevance
“…15,16 In addition, it is possible that FGF23 also regulates the innate immunity. 21,22 A plausible hypothesis is that FGF23 inhibits CYP27B1 in monocytic cells, with subsequent effects on intracellular synthesis of 1,25(OH) 2 D. 21,22,28 In fact, treatment of peripheral blood mononuclear cells isolated from peritoneal dialysate effluents of uremic patients decreased the mRNA expression of CYP27B1 and conversion of 25(OH)D to 1,25(OH) 2 D. 21,22 These biologic effects of FGF23 on monocytic cells support the observation in the present study, which is the first clinical evidence of a relationship between higher serum FGF23 levels and infectious events. Previous observational studies have found similar relationship of serum FGF23 concentration with all-cause mortality but less is known about the longitudinal relationship between serum FGF23 levels with cardiac events in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In addition, it is possible that FGF23 also regulates the innate immunity. 21,22 A plausible hypothesis is that FGF23 inhibits CYP27B1 in monocytic cells, with subsequent effects on intracellular synthesis of 1,25(OH) 2 D. 21,22,28 In fact, treatment of peripheral blood mononuclear cells isolated from peritoneal dialysate effluents of uremic patients decreased the mRNA expression of CYP27B1 and conversion of 25(OH)D to 1,25(OH) 2 D. 21,22 These biologic effects of FGF23 on monocytic cells support the observation in the present study, which is the first clinical evidence of a relationship between higher serum FGF23 levels and infectious events. Previous observational studies have found similar relationship of serum FGF23 concentration with all-cause mortality but less is known about the longitudinal relationship between serum FGF23 levels with cardiac events in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recent studies reported that FGF23 treatment of mononuclear cells isolated from healthy human peripheral blood and peritoneal dialysis effluents from uremic patients decreased the mRNA expression of CYP27B1. 21,22 Accordingly, it is reasonable to hypothesize that circulating FGF23 excess decreases the intracrine production of 1,25(OH) 2 D, which consequently decreases the transcription and the production of cathelicidins 14 leading to an increase in infectious outcomes.…”
mentioning
confidence: 99%
“…Although various effects of increased FGF23 levels with respect to phosphate homeostasis regulation and myocardial hypertrophy have been described, the available evidence for a direct effect of FGF23 on the immune system is very scarce (17). It has been described that FGF23 may inhibit the extrarenal expression of vitamin D-activating enzyme 1α-hydroxylase in monocytes, thus regulating 1,25-dihydroxyvitamin D synthesis (32,33). Moreover, a recently published study among chronic hemodialysis patients demonstrated that increased FGF23 levels were independently associated with a higher infection rate and higher all-cause mortality (18).…”
Section: (G and H)mentioning
confidence: 99%
“…Expression of ferroportin protein was assessed by Western blot analyses using previously reported protocols, 46 involving overnight incubation with primary ferroportin antibody (1/1000; Amgen, Thousand Oaks, CA). A b-actin antibody (Sigma-Aldrich, St. Louis, MO) was used as a loading control.…”
Section: Western Blot and Immunofluorescence Analysesmentioning
confidence: 99%
“…Immunofluorescence analysis of ferroportin and ferritin was carried out using adaptations of previously described methods. 46 Briefly, monocytes or hepatocytes were seeded on 4-well glass slides, and incubated for 1 hour with antibodies to ferroportin (1/200; Amgen) or ferritin (1/200; Abcam). Secondary antibodies labeled with Alexa 594 were applied for 1 hour, and finalized with 49,6-diamidino-2-phenylindole (1/10,000, 5 minutes).…”
Section: Western Blot and Immunofluorescence Analysesmentioning
confidence: 99%